Immune checkpoints in immune response to glioma: two sides of the same coin - Musatova, Oxana; Kumar, Vikas; Vinogradov, Konstantin; Rubtsov, Yury (Frontiers in Immunology, 2025)
Gliomas are aggressive brain tumors of glial origin accounting for about 80% of the central nervous system (CNS) malignancies. Glioma cells are known to form a highly immunosuppressive tumor microenvironment (TME) capable of inhibiting T cell activation and protecting tumors from elimination by the immune system. One of the predominant immune inhibitory mechanisms in the TME are immune checkpoints: a complex system of membrane-bound ligands on tumor and immune cells that interact with surface receptors on T lymphocytes and affect their activation and cytotoxicity. There is mounting evidence regarding the role of immune checkpoints expressed in gliomas, in particular, their most aggressive form – glioblastoma multiforme (GBM). In this review, we discuss the immune checkpoints with proven expression in gliomas, their ligands, related signaling pathways, co-expression profiles, and the effects of immune cells on antitumor activity. We collected data not only on the canonical immune checkpoints (e.g. PD-1/PD-L1 or CTLA-4) but also on novel and alternative ones including soluble mediators and enzymes. We review data describing the correlation of immune checkpoint expression with patient survival as well as co-expression with other molecules involved in glioma development. Where possible, we analyzed the differences between immune checkpoints in low-grade (LGG) and high-grade gliomas (HGG). Negative effects of several immune checkpoints on T cells could be eliminated by therapeutic monoclonal antibodies that block the interaction between checkpoint ligands and receptors. Therefore, alongside with traditional approaches and T cell-based immunotherapy, the antibody-mediated blockade of immune checkpoints could be considered as a potentially promising therapeutic approach against gliomas.